Uniformly Distributed Graphene Domain Grows on Standing Copper via Low-Pressure Chemical Vapor Deposition - Shih-Hao Chan; Sheng-Hui Chen; Wei-Ting Lin; Chien-Cheng Kuo (Advances in Materials Science and Engineering)
Uniformly distributed graphene domains were synthesized on standing copper foil by a low-pressure chemical vapor deposition system. This method improved the distribution of the graphene domains at different positions on the same piece of copper foil along the forward direction of the gas flow. Scanning electron microscopy (SEM) showed the average size of the graphene domains to be about ~20 m. This results show that the sheet resistance of monolayer graphene on a polyethylene terephthalate (PET) substrate is about ~359 /□ whereas that of the four-layer graphene films is about ~178 /□, with a transmittance value of 88.86% at the 550 nm wavelength. Furthermore, the sheet resistance can be reduced with the addition of HNO3 resulting in a value of 84 /□. These values meet the absolute standard for touch sensor applications, so we believe that this method can be a candidate for some transparent conductive electrode applications.